SUGGESTION AND STEREOTYPE IN THE SERVICE OF STATE-CREATING CONTENT - Кияниця, Євгенія (Modern engineering and innovative technologies, 2024)
In the current realities of constant challenges, in particular military aggression, the problem of using suggestion as a tool for shaping state-building narratives is of particular relevance, since suggestive narratives not only influence the behavior of